Preparation method of lithium manganese iron phosphate positive electrode material
Through the two-stage sintering reaction method, the low melting point and high melting point lithium sources are used to promote and control the generation and size of the lithium manganese iron phosphate phase respectively, solving the problem of particle mixing and grading, and improving the compaction density and capacitance of the material.
Patent Information
- Application Number
- CN202510006817.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-18
AI Technical Summary
The existing preparation methods for lithium manganese iron phosphate positive electrode materials are difficult to achieve uniform mixing and grading of particles, resulting in low material compaction density and affecting battery energy density and capacitance.
The two-stage sintering reaction method is adopted, first the first sintering reaction is carried out at low temperature, and the low melting point lithium source is used to promote the formation of lithium manganese iron phosphate phase; then the second sintering reaction is carried out at high temperature, and the particle size is controlled by high melting point lithium source to achieve particle grading.
The uniform mixing and grading of particles is achieved, the compaction density of the material is improved, and the discharge capacity of 0.1C is increased to 160.38mAh/g.
Smart Images

Figure CN119841297A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an electrode material, and in particular to a method for preparing a lithium manganese iron phosphate positive electrode material. Background Art
[0002] Lithium manganese iron phosphate and lithium iron phosphate are both polyanion salts with olivine structure. After the introduction of Mn, the voltage platform of lithium manganese iron phosphate is as high as 4.1V, which is significantly higher than the 3.4V of lithium iron phosphate. Its theoretical energy density is 15% to 20% higher than that of lithium iron phosphate, which can provide electric vehicles with a higher mileage than lithium iron phosphate batteries. Therefore, lithium manganese iron phosphate is one of the upgrade directions of lithium iron phosphate batteries.
[0003] The preparation methods of lithium manganese iron phosphate can be divided into liquid phase method, solid phase method, etc. Among them, the liquid phase method is conducive to regulating the microscopic morphology of the material and improving the uniformity, but it is not conducive to large-scale production; the solid phase method has a high yield, but the solid phase method uses a mechanical method to mix the reactants, which is difficult to achieve atomic-level mixing between the reactants. Reducing the particle size helps to improve the uniformity (Liu Jian et al. "Solution Concentration Assisted Solid Phase Synthesis of Lithium Manganese Iron Phosphate Cathode Materials." Power Technology 3 (2019): 3.), however, reducing the particle size will reduce the compaction density, which in turn affects the energy density of the battery, limiting its energy density advantage. Increasing the grain size is an effective way to increase the compaction density of the material, but due to the low conductivity of the lithium manganese iron phosphate material itself, an excessively large grain size will limit the capacity. At the same time, there are many pores between large-sized grains, which is not conducive to efficient space utilization and reduces its compaction density to a certain extent. Therefore, a single method of increasing the grain size is not suitable for lithium manganese iron phosphate cathode materials. The commonly used method at present is to grade the particles by size, introduce small particles to fill the pores between the large particles, increase the density of the particles, and thus achieve the purpose of increasing the compaction density of the lithium manganese iron phosphate material. Similarly, the mixing of large and small particles is prone to uneven particle size distribution.
[0004] The invention patent application with publication number CN 110474036 A discloses a lithium battery positive electrode material and a preparation method thereof, a lithium battery positive electrode, a lithium battery and a power supply device. By introducing a mixed molten salt, the sintering temperature is divided into two stages according to the eutectic point of the mixed molten salt. The first stage is greater than or equal to the eutectic point temperature and less than the temperature of the second stage. In the first stage sintering, the liquefied mixed molten salt uniformly contacts the lithium source and the precursor, so that the lithium source and the precursor are in more uniform and sufficient contact, and the primary particle size of the ternary material is increased. In the current scheme, the material particle size increases, and there are more pores between large-sized grains, which is not conducive to space utilization and cannot improve the compaction degree of the battery electrode. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a method for preparing lithium manganese iron phosphate positive electrode material to simultaneously achieve uniform mixing and grading of particles.
[0006] Technical solution: The method for preparing a lithium manganese iron phosphate positive electrode material of the present invention comprises the following steps:
[0007] (1) A manganese source, an iron source, a phosphorus source, and a lithium source are selected in a molar ratio of Mn:Fe:P:Li=x:(1-x):1:1.0-1.1, 0.3≤x≤0.7, and 15-25% of a carbon source is selected based on the mass of the product lithium manganese iron phosphate; the lithium source includes a first lithium source and a second lithium source, and the melting point of the first lithium source is lower than that of the second lithium source;
[0008] (2) grinding and mixing the manganese source, the iron source, the phosphorus source, the first phosphorus source, and half of the carbon source, drying, and performing a first sintering reaction to obtain a sintered material, wherein the first sintering reaction temperature is higher than the melting point of the first lithium source and lower than the second sintering reaction temperature;
[0009] (3) Grinding and mixing the sintering material, the second lithium source, and the remaining half of the carbon source, drying, and performing a second sintering reaction to obtain a lithium manganese iron phosphate positive electrode material, wherein the second sintering temperature is lower than the melting point of the second lithium source.
[0010] Preferably, the first lithium source is at least one of lithium hydroxide, lithium nitrate and lithium acetate.
[0011] Preferably, the second lithium source is at least one of lithium carbonate, lithium oxide, lithium phosphate and lithium metaphosphate.
[0012] Preferably, the first sintering reaction temperature is 300-500° C., and the reaction duration is 5-10 hours.
[0013] Preferably, the second sintering reaction temperature is 600-900° C., and the reaction duration is 8-15 hours.
[0014] Preferably, the second sintering temperature is 650-800°C.
[0015] Preferably, the addition ratio of the first lithium source is not less than the addition ratio of the second lithium source.
[0016] Preferably, in step (1), the drying step is performed by spray drying.
[0017] Preferably, in step (1), 0.5≤x≤0.8.
[0018] Preferably, the manganese source is at least one of manganese tetraoxide, manganese carbonate, ferromanganese carbonate, ferromanganese phosphate and ferromanganese hydroxide; the iron source is at least one of ferric oxide, ferric phosphate, ferrous oxalate, ferromanganese carbonate, ferromanganese phosphate and ferromanganese hydroxide.
[0019] Preferably, the phosphorus source is at least one of phosphoric acid, diammonium phosphate, lithium phosphate or monoammonium phosphate.
[0020] Preferably, the carbon source is one or a mixture of glucose, sucrose, polyvinyl alcohol, carbon nanotubes, and graphene.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: uniform mixing and grading of particles are achieved simultaneously: in the first sintering reaction, the temperature is controlled to melt the first lithium source with a low melting point, and the molten part contacts with the manganese, iron, and phosphorus precursors and begins to generate a manganese iron phosphate lithium phase. The amount of the first lithium source added is limited, and the generated manganese iron phosphate lithium phase is also limited; after the second grinding, the first sintered manganese iron phosphate lithium phase, the unreacted manganese, iron, and phosphorus precursors, and the second lithium source are redistributed; in the second sintering reaction, the high melting point characteristics of the second lithium source are utilized to slow down the reaction between the second lithium source and manganese, iron, and phosphorus. The speed at which the precursor material generates the lithium iron manganese phosphate phase makes the particle size of the lithium iron manganese phosphate phase formed by the second sintering reaction relatively smaller. At this time, the size of the lithium iron manganese phosphate generated by the first sintering reaction will continue to increase. The lithium iron manganese phosphate phase generated by the second sintering reaction in turn constrains the lithium iron manganese phosphate generated by the first sintering reaction, controls the particle size, and makes the particle size difference between the lithium iron manganese phosphates generated by the two-stage sintering reactions, thereby realizing particle grading. This method effectively improves the compaction density and solves the problem of reduced capacitance. The compaction density of the prepared lithium iron manganese phosphate reaches 2.38g / cm 3 , the 0.1C discharge capacity can reach 160.38mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is an electron microscope image of lithium manganese iron phosphate prepared in the first embodiment of the present invention. DETAILED DESCRIPTION
[0023] The technical solution of the present invention is further described below in conjunction with embodiments.
[0024] Embodiment 1:
[0025] (1) Molar ratio (calculated by element) Mn:Fe:P:Li 1 :L i2 =0.6:0.4:1:0.75:0.3 Weigh manganese tetraoxide, iron phosphate, phosphoric acid, lithium hydroxide (Li 1 ) and lithium carbonate (Li 2 ), and weigh 20% of the theoretical production of lithium manganese iron phosphate glucose;
[0026] (2) placing manganese tetraoxide, iron phosphate, phosphoric acid, lithium hydroxide and 10% glucose in deionized water, mixing, grinding and drying to obtain a first precursor;
[0027] (3) calcining the first precursor at 500° C. for 10 h in an inert gas environment, cooling it naturally to room temperature, and then taking it out to obtain a sintered material;
[0028] (4) placing the first precursor, lithium carbonate and the remaining 10% glucose in deionized water, mixing, grinding and drying to obtain a second precursor;
[0029] (5) The second precursor was calcined at 650° C. for 10 h in an inert gas environment, and then naturally cooled to room temperature and taken out to obtain a lithium manganese iron phosphate positive electrode material.
[0030] Embodiment 2:
[0031] (1) Molar ratio (calculated by element) Mn:Fe:P:Li 1 :L i2 =0.6:0.4:1:0.55:0.5 Weigh manganese tetraoxide, iron phosphate, phosphoric acid, lithium hydroxide (Li 1 ) and lithium carbonate (Li 2 ), and weigh 20% of the theoretical production of lithium manganese iron phosphate glucose;
[0032] (2) placing manganese tetraoxide, iron phosphate, phosphoric acid, lithium hydroxide and 10% glucose in deionized water, mixing, grinding and drying to obtain a first precursor;
[0033] (3) calcining the first precursor at 500° C. for 8 h in an inert gas environment, cooling it naturally to room temperature, and taking it out to obtain a sintered material;
[0034] (4) placing the first precursor, lithium carbonate and the remaining 10% glucose in deionized water, mixing, grinding and drying to obtain a second precursor;
[0035] (5) The second precursor was calcined at 680° C. for 12 h in an inert gas environment, and then naturally cooled to room temperature and taken out to obtain a lithium manganese iron phosphate positive electrode material.
[0036] Embodiment 3:
[0037] (1) Molar ratio (calculated by element) Mn:Fe:P:Li 1 :L i2 =0.6:0.4:1:0.35:0.7 Weigh manganese tetraoxide, iron phosphate, phosphoric acid, lithium hydroxide (Li 1 ) and lithium oxide (Li 2 ), and weigh 20% of the theoretical production of lithium manganese iron phosphate glucose;
[0038] (2) placing manganese tetraoxide, iron phosphate, phosphoric acid, lithium hydroxide and 10% glucose in deionized water, mixing, grinding and drying to obtain a first precursor;
[0039] (3) calcining the first precursor at 500° C. for 5 h in an inert gas environment, cooling it naturally to room temperature, and obtaining a sintered material;
[0040] (4) placing the first precursor, lithium oxide and the remaining 10% glucose in deionized water, mixing, grinding and drying to obtain a second precursor;
[0041] (5) The second precursor was calcined at 800° C. for 15 h in an inert gas environment, and then naturally cooled to room temperature and taken out to obtain a lithium manganese iron phosphate positive electrode material.
[0042] Comparative Example 1: Compared with Example 1, only the second sintering reaction temperature is changed, and the second sintering reaction temperature is 750°C.
[0043] Comparative Example 2:
[0044] (1) Manganese tetraoxide, iron phosphate, phosphoric acid and lithium hydroxide are weighed in a molar ratio (calculated by element) of Mn:Fe:P:Li=0.6:0.4:1:1.05, and glucose of 20% of the theoretical production of lithium manganese iron phosphate is weighed;
[0045] (2) placing manganese tetraoxide, iron phosphate, phosphoric acid, 0.75 parts of lithium hydroxide in step (1) and 10% glucose in deionized water, mixing, grinding and drying to obtain a first precursor;
[0046] (3) calcining the first precursor at 500° C. for 10 h in an inert gas environment, cooling it naturally to room temperature, and then taking it out to obtain a sintered material;
[0047] (4) placing the first precursor, the remaining 0.3 parts of lithium hydroxide and the remaining 10% of glucose in deionized water, mixing, grinding and drying to obtain a second precursor;
[0048] (5) The second precursor was calcined at 650° C. for 10 h in an inert gas environment, and then naturally cooled to room temperature and taken out to obtain a lithium manganese iron phosphate positive electrode material.
[0049] Comparative Example 3:
[0050] (1) Manganese tetraoxide, iron phosphate, phosphoric acid and lithium carbonate are weighed in a molar ratio (calculated by element) of Mn:Fe:P:Li:Li=0.6:0.4:1:1.05, and glucose of 20% of the theoretical production of lithium manganese iron phosphate is weighed;
[0051] (2) placing manganese tetraoxide, iron phosphate, phosphoric acid, 0.75 parts of lithium carbonate in step (1) and 10% glucose in deionized water, mixing, grinding and drying to obtain a first precursor;
[0052] (3) calcining the first precursor at 740° C. for 10 h in an inert gas environment, cooling it naturally to room temperature, and then taking it out to obtain a sintered material;
[0053] (4) placing the first precursor, the remaining 0.3 parts of lithium carbonate and the remaining 10% of glucose in deionized water, mixing, grinding and drying to obtain a second precursor;
[0054] (5) The second precursor was calcined at 740° C. for 10 h in an inert gas environment, and then naturally cooled to room temperature and taken out to obtain a lithium manganese iron phosphate positive electrode material.
[0055] Comparative Example 4: Compared with Comparative Example 3, only the second sintering reaction temperature is changed, and the second sintering reaction temperature is 650°C.
[0056] The lithium manganese iron phosphate positive electrode materials obtained in the above examples 1-3 and comparative examples 1-4 were prepared into button cells by the following method and the electrochemical performance was evaluated:
[0057] The lithium manganese iron phosphate positive electrode material, Super P (conductive carbon black) and PVDF were uniformly mixed in a NMP solution at a ratio of 8:1:1 to obtain a mixed slurry, which was applied on a bright aluminum foil by hand coating and then dried at 100°C. After the NMP was completely volatilized, the electrode was punched into an electrode sheet with a diameter of 13 mm, and then the electrode sheet was placed in a vacuum oven at 105°C to dry overnight. After weighing the electrode sheet, it was quickly transferred to a glove box, with metallic lithium as the counter electrode, Celgard 2400 as the diaphragm, and the electrolyte was 1 mol / L LiPF 6 The assembled battery was dissolved in a mixed solvent of EC / DMC / EMC (volume ratio of 1:1:1), and the electrochemical performance of the battery was tested. The charge and discharge behaviors of the button battery were tested and analyzed by the Xinwei test system using constant current-constant voltage charge (CC-CV) and constant current discharge (DC) test methods. The test voltage range was 2.0-4.35V. The compaction density of the lithium manganese iron phosphate cathode material was tested according to GBT30835-2014 using PRCD1100 powder compaction test equipment. The test results are shown in Table 1.
[0058] Table 1 Electrochemical performance characterization (button cell) and compaction density of materials of Examples 1-3 and Comparative Examples 1-3
[0059]
[0060] In Comparative Example 1, the temperature of the second sintering reaction is higher than the melting point of lithium carbonate, and the discharge capacity drops significantly. The reason for this result may be that the particles sintered above the melting point tend to grow in size, and large particles are not conducive to lithium ion transmission, which limits the capacity. When sintered below the melting point, the particles tend to form small particles; in Comparative Example 4, a lithium source is used and added in batches, and the first batch of sintering temperatures are controlled above the melting point of the lithium source, and the second sintering temperature is below the melting point, but the discharge capacity is not improved. The reason is that the first sintering temperature is too high. During the first sintering process, the high temperature drives the particles to grow larger, and the precursor of lithium iron manganese phosphate that is not generated at a higher temperature may melt and combine with lithium iron manganese phosphate, resulting in further promotion of particle growth in the second sintering. As a result, large particles occupy a larger part, resulting in the inability to release capacity, and no large and small particle grading is formed, so the compaction density is not significantly improved; in Comparative Examples 2 and 3, a lithium source is used and added in batches. Both sinterings are above the melting point. Compared with Examples 1 and 2, the compaction density and 0.1C discharge capacity are lower. Figure 1 As shown, it is the SEM image of the lithium iron manganese phosphate positive electrode material obtained in this embodiment 1. It can be seen in the figure that the lithium iron manganese phosphate positive electrode material prepared in this embodiment 1 is a dense particle composed of large and small particle gradings, indicating that by using different lithium sources and controlling the sintering temperature according to the melting point of the lithium source, a lithium iron manganese phosphate positive electrode material with large and small particle gradings can be formed, thereby improving the compaction performance and electrical performance of the positive electrode material at the same time.
Claims
1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The following steps are involved: (1) A manganese source, an iron source, a phosphorus source, and a lithium source are selected in a molar ratio of Mn:Fe:P:Li=x:(1-x):1:1.0-1.1, 0.3≤x≤0.7, and 15-25% of a carbon source is selected based on the mass of the product lithium manganese iron phosphate; the lithium source includes a first lithium source and a second lithium source, and the melting point of the first lithium source is lower than that of the second lithium source; (2) grinding and mixing the manganese source, the iron source, the phosphorus source, the first phosphorus source, and half of the carbon source, drying, and performing a first sintering reaction to obtain a sintered material, wherein the first sintering reaction temperature is higher than the melting point of the first lithium source and lower than the second sintering reaction temperature; (3) Grinding and mixing the sintering material, the second lithium source, and the remaining half of the carbon source, drying, and performing a second sintering reaction to obtain a lithium manganese iron phosphate positive electrode material, wherein the second sintering temperature is lower than the melting point of the second lithium source.
2. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The first lithium source is at least one of lithium hydroxide, lithium nitrate and lithium acetate.
3. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The second lithium source is at least one of lithium carbonate, lithium oxide, lithium phosphate, and lithium metaphosphate.
4. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The first sintering reaction temperature is 300-500° C., and the reaction duration is 5-10 hours.
5. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The second sintering reaction temperature is 600-900° C., and the reaction duration is 8-15 hours.
6. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 5, characterized in that: The second sintering temperature is 650-800°C.
7. The method for preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The addition ratio of the first lithium source is not less than the addition ratio of the second lithium source.
8. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In step (1), the drying step is performed by spray drying.
9. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In step (1), 0.5≤x≤0.
8.
10. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The manganese source is at least one of manganese tetraoxide, manganese carbonate, ferromanganese carbonate, ferromanganese phosphate and ferromanganese hydroxide; the iron source is at least one of ferric oxide, ferric phosphate, ferrous oxalate, ferromanganese carbonate, ferromanganese phosphate and ferromanganese hydroxide; the phosphorus source is at least one of phosphoric acid, diammonium phosphate, lithium phosphate or monoammonium phosphate; the carbon source is a mixture of one or more of glucose, sucrose, polyvinyl alcohol, carbon nanotubes and graphene.
Citation Information
Patent Citations
Lithium battery anode material and manufacturing method thereof, lithium battery anode, lithium battery and power supply device
CN110474036A
Cited By
Preparation method of lithium manganese iron phosphate positive electrode material
CN120600806A
Preparation method of lithium manganese iron phosphate positive electrode material
CN120600806B
Lithium manganese iron phosphate precursor as well as preparation method and application thereof
CN121376954A